Prevalence of metabolic syndrome among patients with superficial mycotic infections in a tertiary care hospital - Mannan, Shamsun N. B.; Bakar, Muhammad A.; Mamun, Shaikh H.; Biswas, Rajat S. R.; Hossain, Istiaque (International Journal of Research in Dermatology, 2020)
Background: Incidence of metabolic syndrome and superficial mycotic infection is progressively increasing worldwide. Skin disorders, usually neglected and frequently underdiagnosed in patients with metabolic syndrome. So, the objective of the study is to linkup between metabolic syndrome and superficial mycotic infections. Methods: Total 300 diagnosed patients of superficial mycotic infection out of 1000 patients in a 5 months period from January 2019 to May 2019 who gave consent were chosen at random from the patients attending the OPD consultancy. Thorough clinical evaluation and routine hematological investigations, oral glucose tolerance test (OGTT), fasting lipid profile were tested and BMI and blood pressure were recorded to diagnose metabolic syndrome. Fungal infections were confirmed by KOH mount. Results: Among 1000 patients attended in OPD consultancy, majority of the patients were female (60%). Among them 300 patients have got different superficial fungal infections (female was 223 and male 77). Among this 300-study population, age variation is significant. There were highest female patients in age group from 36 yrs- 45 yrs. Tinea corporis was the most frequent fungal infection in female (65%), Tinea cruris is highest in male (21%). The most alarming is that among that 300 patients 45% patients have got raised OGTT,91% patient has increased BMI, female predominant. 59.3% has raised blood pressure and increased serum cholesterol in 70.1% patients. Conclusions: Superficial fungal infections are epidemic worldwide. In our study the new era is that presence of metabolic syndrome among patients with superficial mycotic infections. So early detection and treatment of metabolic syndrome helps in cure of superficial mycotic infections.